Human leukocyte antigen class I and class II alleles are associated with susceptibility and resistance in borderline leprosy patients from Southeast Brazil - de Souza-Santana, Fabiana Covolo (BMC Infect Dis, 2015)
BACKGROUND: Evidence suggests that human leukocyte antigen (HLA) alleles influence the host immune response against Mycobacterium leprae. However, the association between HLA alleles and borderline (B) leprosy has not been studied. The aim of this study was to determine whether HLA class I and II molecules are associated with susceptibility or resistance to B leprosy including borderline-tuberculoid (BT), borderline-borderline (BB), and borderline-lepromatous (BL). METHODS: DNA was obtained by the salting-out technique from the blood samples of 202 patients with B leprosy and 478 control subjects. HLA class I (A*, B*, and C* loci) and class II (DRB1* and DQB1* loci) genotypes were determined by polymerase chain reaction amplification and reverse hybridization with sequence-specific oligonucleotide probes and sequence-specific primers. RESULTS: The case-controlled analysis results showed a significant association between B leprosy and HLA-C*05 (5.94% vs. 14.02%; p = 0.002, OR = 0.38, 95% CI = 0.20–0.73, pc = 0.032) and HLA-DRB1*07 (16.34% vs. 26.77%; p = 0.003, OR = 0.53, 95% CI = 0.3–0.8, pc = 0.039). A protective association was observed between BL leprosy and HLA-DQB1*02 (18.18% vs. 39.53%; p = 0.005, OR = 0.34, 95% CI = 0.15–0.75, pc = 0.025). In reactional patients, a significant association was observed between HLA-B*15 (28.72% vs. 12.76%; p = 0.011, OR = 2.75, 95% CI = 1.30–5.85, pc = 0.352) and predisposition to reversal reaction. Haplotype analysis showed that A*02-B*07-C*07-DRB1*15-DQB1*06 (2.97% vs. 1.04%; p = 0.015) and A*02-B*40-C*03-DRB1*13-DQB1*06 (1.73% vs. 0.10%; p = 0.0011) were associated with susceptibility to the B form. The presence of the HLA-DRB1*02 or HLA-DRB1*03/HLA-DQB1*01 haplotypes in B patients (22.05% vs. 33.0%; p = 0.005) suggested the involvement of these haplotypes in this clinical form of the disease. CONCLUSIONS: The results indicate the involvement of HLA class I and class II molecules in B leprosy and reversal reactions; it also suggest a role for HLA in polarization of the disease in this group of patients. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12879-015-0751-0) contains supplementary material, which is available to authorized users.